1995
DOI: 10.1515/bchm3.1995.376.12.723
|View full text |Cite
|
Sign up to set email alerts
|

New Data on Content and Distribution of Gangliosides in Human Milk

Abstract: The content and distribution of gangliosides, and total lipid content, were studied in human milk samples from different periods of lactation. We found a significant correlation (r = 0.5564; p = 0.0165) between ganglioside and total lipid contents. There was a selective change in the relative concentrations of GD3 and GM3 during lactation. The most abundant ganglioside in samples from the first three weeks of lactation was GD3, whereas after the first month, GM3 was the major ganglioside. In addition to GD3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 34 publications
7
39
1
Order By: Relevance
“…These re sults agree with those published until now, because the content of gangliosides in human milk from Swedish mothers [6] was different from that reported for Japanese [8] and for Spanish mothers [9], However, the distribu tion of individual gangliosides, at least of the two main (Gm3 and GD.0, was similar in these studies mentioned [6,8,9],…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These re sults agree with those published until now, because the content of gangliosides in human milk from Swedish mothers [6] was different from that reported for Japanese [8] and for Spanish mothers [9], However, the distribu tion of individual gangliosides, at least of the two main (Gm3 and GD.0, was similar in these studies mentioned [6,8,9],…”
Section: Discussionsupporting
confidence: 88%
“…In Spanish as well as in Panamanian milk the relative content of G 1 (Gm3) increased, and the rela tive content of G3 (Gd3) decreased as lacta tion progressed. This selective change of the proportions of Gm3 and Gd3 is characteristic of human milk and has been described before by other authors [8] and by us [9],…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The ganglioside composition of milk fat from mammalian species can di!er markedly (Plantz and Patton, 1973;Laegreid et al, 1986;Puente et al, 1996), and the ganglioside content of a given milk can change during lactation (Takamizawa et al, 1986a;Puente et al, 1994Puente et al, , 1995Rueda et al, 1995;Pan and Izumi, 1999). Unique gangliosides have been found in buttermilk (Huang, 1973;Takamizawa et al, 1986b;Ren et al, 1992), suggesting cultured dairy products may show other variations.…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of the disialoganglioside (GD)GD 3 has been detected in developing tissues (Ando, 1983), as well as in human colostrum, and this latter fact may reflect a biological role in the development of organs such as the intestine in the neonate. Human milk also contains significant amounts of highly polar gangliosides (Rueda et al 1995). It has been suggested that complex gangliosides in developing tissues act as mediators of specific types of cell-contact interactions during the early stages of mammalian development (Friedman et al 1983).…”
mentioning
confidence: 99%